Administration of Live-Attenuated Newcastle Disease (ND) Vaccines Derived from B1 and LaSota Strain and Their Effect on Broiler Antibody Titers - A. Rianti Rhasinta Alifha; Fedri Rell; Trini Purnamasari Syahid; Satya Apada, Andi Magfirah (Hasanuddin University, 2022)
Newcastle Disease is a contagious disease caused by Avian Paramyxovirus and infects different types of poultries including broiler. Vaccination as a preventive effort against the ND virus could employ both attenuated and inactivated vaccines. This study aims to identify the effect of administering live-attenuated LaSota and B1 ND vaccines against broiler antibody titers. This experiment employed 54 DOCs and was divided into 3 groups of treatments. Vaccination was performed at the age of 3 days old through eye drop administration. Blood specimens were taken from vena brachialis at the age of 7, 14, 21 days old. Hemagglutination Inhibition (HI) assay was analyzed using One-Way Analysis of Variance (ANOVA) followed by Least Significant Different (LSD) test if the probability is significant (P<0.05). The data of Immune Percentage is presented using descriptive quantitative analysis. The research results demonstrated that live-attenuated LaSota ND vaccination at the age of 3 days could sustain and induce immunity until the age of 21 days while B1 ND vaccination at the age of 3 days could only sustain immune protection until the age of 14 days. Live-attenuated LaSota and B1 ND vaccines did not have any significant effect on the broiler antibody titers. Keywords: Broiler, Newcastle Disease (ND), LaSota vaccine, B1 vaccine, Hemagglutination test, Hemagglutination Inhibition Test